Hybrid GEO-PO Algorithm for Dual-Input Wireless Power Transfer and Photovoltaic-Fed DC-DC Converter in Electric Vehicle Charging Applications - Mattaparthi, Ganesh Babu; P, Srinivasa Rao Nayak (Revista IEEE América Latina, 2025)
The increasing demand for efficient and sustainable electric vehicle (EV) charging solutions has driven the development of advanced multi-input charger systems. This paper introduces a closed-loop EV charger powered by dual energy inputs, i.e., wireless power transfer (WPT) and photovoltaic (PV) sources. The dual-input charger integrates these energy sources to ensure stable and efficient constant voltage battery charging. The output voltage is continuously compared with the required EV battery charging voltage and regulated using a proportional-integral (PI) controller. To address the nonlinear and dynamic characteristics of the input sources, a novel Hybrid GEO-PO optimization algorithm, which combines the strengths of the Golden Eagle Optimizer (GEO) and the Puma Optimizer (PO), is proposed to determine the optimal PI controller parameters. MATLAB/Simulink simulations and experimental validation demonstrate that the Hybrid GEO-PO algorithm outperforms its parent algorithms in regulating EV battery charging voltage. The hybrid algorithm achieves faster response times, lower overshoot, and enhanced robustness compared to the standalone GEO and PO algorithms. Additionally, the successful implementation of the system using an FPGA controller highlights its practicality and suitability for real-world applications. This study establishes the Hybrid GEO-PO algorithm as a superior and promising approach for optimizing dual-input EV chargers, paving the way for next-generation intelligent charging infrastructure.